Anosognosia in HD: Comparison of self-report and caregiver ratings with objective performance measures. (February 2023) - Hughes, Shelby B.; Churchill, Emma; Smirnova, Anna; Hall, Andrew; Culbert, Braden; Snell, Chase; Wright, Brenton A.; Gilbert, Paul E.; Corey-Bloom, Jody
Abstract: Introduction: Individuals with Huntington's disease (HD) commonly experience anosognosia, a lack of awareness of deficits. Thus, it is important to examine the accuracy of patient vs caregiver ratings on the basis of objective performance-based measures. Methods: The Anosognosia Scale (AS) was given to 33 patients with manifest HD and their caregivers. The AS consists of 8 items in which individuals rate their global abilities relative to same-aged peers. Scores range from very impaired to excellent. Caregiver and patient ratings were then correlated with objective measures. Results: Caregivers' evaluations of patients' cognitive and motoric abilities were more highly correlated with objective measures than patients' ratings. Specifically, caregivers' AS item scores were highly correlated with objective measures of walking (Unified Huntington Disease Rating Scale (UHDRS) tandem walking score [r = 0.57, p = .001] vs. patient [r = 0.39, p = .031]); dexterity (UHDRS pronation supination score [r = 0.55, p = .011] vs. patient [r = 0.18, p = .393]); speech (UHDRS dysarthria score [r = 0.55, p = .004] vs. patient [r = 0.03, p = .854]); memory (MoCA score [r = -.45, p = .048] vs. patient [r = -.11, p = .963]); attention (Trails Making Test A score [r = 0.58, p = .004] vs. patient [r = 0.08, p = .686]); and word retrieval (category fluency ([r = -.58, p = .004] vs. patient [r = -.02, p = 1.00]). Moreover, both the UHDRS total motor score (TMS) (F(1, 29) = 7.50, p = .010) and the Mini Mental Status Exam (MMSE) (F(1, 31) = 5.40, p = .027) were significant predictors of patient levels of anosognosia. Conclusions: Our findings indicate that caregivers may be better able to rate HD patients' cognitive and motor abilities than patients themselves. Both cognitive and motor severity are significant predictors of levels of anosognosia in HD. Highlights: Caregiver-ratings of HD functioning better correlate with objective measures. Anosognosia impairs HD self-report of cognitive and motoric abilities. Cognitive and motoric severity are predictors of anosognosia levels in HD.